Pomoże ktoś ?
1) Uporządkuj jednomiany:
a) 4x⋅6x =
b) 3x⋅(–6x2) =



2) Uprość wyrażenia:
a) 10x + 4x =
b) 3y + y + 4y =
c) – 13b + 4b – 5b – 4a =
d) 4p + 9p2 – 7p – 2p2 =
e) (2x – 3) – 8x =
f) – (2x – y) + (y – 2x) =
g) 6(2x + 7) =
h) x(4x – 7) =
i) 3x(9 – 5x) =
j) 5(5x – 4) – 4(3x – 6) =



Odpowiedź :

Odpowiedź:

1)

a) 4x * 6x = 24x²

b) 3x * (- 6x²) = - 18x³

2)

a) 10x + 4x = 14x

b)  3y + y + 4y = 8y

c)  - 13b + 4b - 5b - 4a = - 4a - 14b

d)  4p + 9p² - 7p - 2p² = 7p² - 3p

e)  (2x - 3) - 8x = 2x - 3 - 8x = - 6x - 3

f)  - (2x - y) + (y - 2x) = - 2x + y + y - 2x = - 4x + 2y

g) 6(2x + 7) = 12x + 42

h)  x(4x - 7) = 4x² - 7x

i)  3x(9 - 5x) = 27x - 15x²

j)  5(5x - 4) - 4(3x - 6) = 25x - 20 - 12x + 24 = 13x + 4